WALKING WALKING TOUR ORGANIZER: AN INDONESIAN TRAVEL AGENT GOES INTERNATIONAL - Maulana Muhammad; Fitri Anggreni Kusuma; Dewi Apriliani; Ingrid Claudia Elianne Inthe; Mikhael Zulfikar Rizqillah Hakim; Santi Diyanisa; Hala Shaud Alrashidi (AIBPM Publisher, 2017)
Walking Walking Tour Organizer is tour service located in Malang, East Java, Indonesia. So far Walking Wlaking Tour Organizer mostly serve consumer in Malang. Walking Walking Tour Organizer have commitment want to be a company could be worldwide.Asian country should be very good for target market because most of the total of tourist visiting Indonesia is from Asian country.